2016
DOI: 10.3233/cbm-160624
|View full text |Cite
|
Sign up to set email alerts
|

KRAS, BRAF oncogene mutations and tissue specific promoter hypermethylation of tumor suppressor SFRP2, DAPK1, MGMT, HIC1 and p16 genes in colorectal cancer patients

Abstract: Results of the current study have confirmed that KRAS mutations and SFRP2 hypermethylation can be used as genetic markers in colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…However, hormone replacement therapy does not significantly affect PGR methylation [48], and the protective effect of hormone replacement therapy may be due to oestrogen receptor rather than progesterone receptor function. HIC1 has been investigated mainly as part of a CIMP panel [49], but its methylation is not associated with clinicopathologic features [50]. EN1 methylation is also not associated with clinicopathologic features [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, hormone replacement therapy does not significantly affect PGR methylation [48], and the protective effect of hormone replacement therapy may be due to oestrogen receptor rather than progesterone receptor function. HIC1 has been investigated mainly as part of a CIMP panel [49], but its methylation is not associated with clinicopathologic features [50]. EN1 methylation is also not associated with clinicopathologic features [51].…”
Section: Discussionmentioning
confidence: 99%
“…As a WNT signaling-associated EMT modulator, SFRP2 is down-regulated in various malignancies due to the promoter hypermethylation 21. Typically, the methylation status of SFRP2 gene is a tumor-specific epigenetic marker in human breast cancer and CRC,22,23 which may play a central role in the chemoprevention of CRC 24. Besides, it is also the critical paracrine factor released by the AKT-mesenchymal stem, which can mediate myocardial survival and repair 25.…”
Section: Discussionmentioning
confidence: 99%
“…DAPK1 acts as a tumor suppressor to play a rate-limiting effector in an endoplasmic reticulum (ER) stress-dependent apoptotic pathway [23]. Its expression is epigenetically suppressed in several tumors [24]. Lee et al [10] reported that DAPK1 acts as a kinase responsible for the phosphorylation of Pin 1 on Ser71 in the catalytic active site.…”
Section: Discussionmentioning
confidence: 99%
“…DAPK1 acts as a tumor suppressor to play a rate‐limiting effector in an endoplasmic reticulum (ER) stress‐dependent apoptotic pathway . Its expression is epigenetically suppressed in several tumors . Lee et al.…”
Section: Discussionmentioning
confidence: 99%